Facile preparation of alkali metal‐modified hollow nanotubular manganese‐based oxide catalysts and their excellent catalytic soot combustion performance - Chunlei Zhang; Siyu Gao; Xinyu Chen; Di Yu; Lanyi Wang; Xiaoqiang Fan; Ying Cheng; Xuehua Yu; Zhen Zhao (Smart Molecules)
Abstract The soot emitted during the operation of diesel engine exhaust seriously threatens the human health and environment, so treating diesel engine exhaust is critical. At present, the most effective method for eliminating soot particles is post‐treatment technology. Preparation of economically viable and highly active soot combustion catalysts is a pivotal element of post‐treatment technology. In this study, different single‐metal oxide catalysts with fibrous structures and alkali metal‐modified hollow nanotubular Mn‐based oxide catalysts were synthesized using centrifugal spinning method. Activity evaluation results showed that the manganese oxide catalyst has the best catalytic activity among the prepared single‐metal oxide catalysts. Further research on alkali metal modification showed that doping alkali metals is beneficial for improving the oxidation state of manganese and generating a large number of reactive oxygen species. Combined with the structural effect brought by the hollow nanotube structure, the alkali metal‐modified Mn‐based oxide catalysts exhibit superior catalytic performance. Among them, the Cs‐modified Mn‐based oxide catalyst exhibits the best catalytic performance because of its rich active oxygen species, excellent NO oxidation ability, abundant Mn4+ ions (Mn4+/Mnn+ = 64.78%), and good redox ability. The T10, T50, T90, and CO2 selectivity of the Cs‐modified Mn‐based oxide catalyst were 267°C, 324°C, 360°C, and 97.8%, respectively.